Halal Validation and Product Quality as Added Value for Risoles SMEs in Samarinda City: Validasi Kehalalan dan Kualitas Produk sebagai Nilai Tambah UMKM Risoles di Kota Samarinda - Ilham, Muhammad Fauzan Nur; Pranoto, Wawan Joko; Reza, Andi; Nurdin, Andi; Alam, Aksal Illal Al; Halim, Abdul (Wadah Inovasi Indonesia, 2023)
This community service initiative addresses the critical need for halal certification and quality assurance in Risoles SMEs to enhance consumer trust and market competitiveness. The study employed a mixed-method approach, combining observational analysis of production processes, ingredient validation, and stakeholder interviews. Key findings reveal that rigorous halal validation of raw materials (e.g., mayonnaise, cheese, and frying oil) and hygiene-compliant production practices significantly improved consumer confidence. Post-intervention sales increased by 35%, attributed to transparent halal labeling and quality guarantees. The proposed solution includes standardized halal documentation frameworks and continuous quality control training for SMEs. These efforts align with Indonesia’s growing demand for halal-certified food products, offering a replicable model for similar SMEs.